Calidad en el servicio online como estrategia en las empresas Latinoamericanas (2021)
This research is carried out in the theory of Quality of Service, as a fundamental pillar in customer satisfaction, so its focus is directed on the development of the different quality models exposed over time, explaining the contributions of the writers and highlighting the cases applied. As for the methodology of searching and selecting the existing literature in the systematic review articles, a process is carried out supported by criteria and filters such as the search algorithms used with keywords. From that, a series of data are introduced which were obtained from the bibliographic sources that show what is happening with these topics over the last 5 years. Based on the data and information collected, it can be observed that quality presents various approaches and updates to the models.